2020
DOI: 10.1007/s40199-020-00327-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glycoproteins as a therapeutic strategy for diabetes mellitus and its complications

Abstract: Objectives Glycoproteins are organic compounds formed from proteins and carbohydrates, which are found in many parts of the living systems including the cell membranes. Furthermore, impaired metabolism of glycoprotein components plays the main role in the pathogenesis of diabetes mellitus. The aim of this study is to investigate the influence of glycoprotein levels in the treatment of diabetes mellitus. Methods All relevant papers in the English language were compiled by searching electronic databases, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 243 publications
(264 reference statements)
0
16
0
Order By: Relevance
“…For example, O -glycans without sialic acids and fucoses were barely found in the obese and diabetic group. It has been reported that the process of the Mucin type glycosylation formation is catalyzed by N -acetylgalactosaminyl transferases (GalNAc-transferases) from a family of uridine diphosphate- N -acetylgalactosamine [ 61 ]. A lack of expression or low expression of certain O -glycans may be related to the activity of GalNAc-transferases, which could possibly be influenced by the obese and diabetic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, O -glycans without sialic acids and fucoses were barely found in the obese and diabetic group. It has been reported that the process of the Mucin type glycosylation formation is catalyzed by N -acetylgalactosaminyl transferases (GalNAc-transferases) from a family of uridine diphosphate- N -acetylgalactosamine [ 61 ]. A lack of expression or low expression of certain O -glycans may be related to the activity of GalNAc-transferases, which could possibly be influenced by the obese and diabetic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, efforts have been made to conjugate existing and new pharmaceuticals to various glycans to enhance stability, safety and clinical efficacy [8]. Differential glycosylation is being profiled in diseases to be developed as novel vaccine or drug targets [25]. Attempts have been made to change glycosylation patterns of immune components to boost the body's inherent strength to fight infection and diseases [27].…”
Section: Resultsmentioning
confidence: 99%
“…See Figure 2 for a diagram depicting this mechanism. Aside from tumours, glycoprotein pattern recognition has also been studied for its potential use in treating diabetes mellitus and its long-term complications [25]. The abnormal metabolism of glycoproteins and its derivatives contributes greatly to the pathogenesis and progression of diabetes.…”
Section: Targeting Glycosylation For Vaccine and Drug Developmentmentioning
confidence: 99%
“…In the human body polyprenols are metabolised into dolichols and dolichyl phosphate by enzymatic catalysis 11 . In humans, dolichols regulate the permeability and stability of membranes, partaking in the biosynthesis of human glycoproteins 11 , 12 . Both dolichols and polyprenols are found in the form of esters, carboxylic acids and free alcohol in the cell 13 , while a small portion is found in the form of phosphates 14 .…”
Section: Introductionmentioning
confidence: 99%